Batchsubmit: a high‐volume batch submission system for earthquake engineering simulation‡. (5th March 2014) - Mohan, Anup; Hacker, Thomas; Rodgers, Gregory P.; Islam, Tanzima; Wilkins‐Diehr, Nancy; Majumdar, Amit
SUMMARY Network for Earthquake Engineering Simulation (NEES) is a network of 14 earthquake engineering labs distributed across the USA. As a part of the NEES effort NEESComm operates a comprehensive cyberinfrastructure that consists of the NEEShub and the NEES Project Warehouse. NEESComm provides consistent access to several high performance computing (HPC) venues. These venues include Extreme Science and Engineering Discovery Environment, the Open Science Grid, Purdue Supercomputers, and NEEShub servers. In this paper, we describe the system we developed, batchsubmit, which allows NEES researchers to make use of all these venues through the NEEShub science gateway. Copyright © 2014 John Wiley & Sons, Ltd.